Constructing Idealised Okinawa : Projected Image of Okinawa and Okinawans in the Context of Tourism - Sipilä, Eve (My University, 2026)
This Master’s thesis examines the projected image of Okinawa and Okinawans in the context of tourism. Projected image is a destination image that is constructed by tourism supply-side actors, such as a destination marketing organization. This study analyses the official Be.Okinawa tourism website using qualitative content analysis as the research method. As the website is affiliated with Okinawa Prefecture, its projected images are assumed to reflect how Okinawa Prefecture seeks to present Okinawa and Okinawans to Japanese and international audiences. Okinawa is Japan’s southernmost prefecture inhabited by Okinawans, originally an indigenous people with their own language and culture. Throughout history representations of Okinawa and Okinawans have been strongly shaped by external actors – most notably China, Japan, and the United States – rather than by Okinawans themselves. As today Okinawa is known as a popular tourist destination, it is important to understand contemporary representations of Okinawa and Okinawans in this context. The findings indicate that while the projected tourism images of Okinawa and Okinawans are positive, they are mostly stereotypical. The focus on tropical paradise-like nature and unique culture is similar to the media representations of Okinawa during the Okinawa boom. Okinawans are portrayed to live an idealised, traditional lifestyle in communities with a high proportion of elderly people. Yet, Okinawa is also presented in a modern light with top-notch research and new business created by innovative Okinawans. Nevertheless, societal and politically sensitive issues remain largely absent. The study concludes that although culture has an important role for Okinawans in multiple ways, cultural soft sell through tourism and media is unlikely to enhance Okinawans’ political agency. Instead, it is suggested that Okinawa Prefecture could create a deeper sense of place by including more local Okinawans in the construction of its projected tourism image. This way Okinawa could promote greater plurality and bring visibility to currently neglected sociopolitical and environmental issues. Furthermore, it is demonstrated that analysing projected images in historical, sociopolitical, and cultural contexts is particularly important in case of Okinawa. The image projected by Okinawa Prefecture may be influenced by surrounding power relations even today. These observations are in line with social constructionism as the guiding research paradigm of this thesis. Finally, it is noted that a single actor like Okinawa Prefecture cannot fully control Okinawa’s projected tourism image alone. Instead, multiple historical and contemporary constructions of Okinawa and Okinawans continue to coexist also in future.
Keywords: Okinawa, projected destination image, tourism, Okinawa boom, Japan, sense of place, Okinawan, destination image, destination marketing organization, social constructionism